2006
DOI: 10.1007/s00228-006-0139-6
|View full text |Cite
|
Sign up to set email alerts
|

The relative bioavailability of loratadine administered as a chewing gum formulation in healthy volunteers

Abstract: Our study showed that formulation of loratadine as a medicated chewing gum results in an almost threefold increase in relative bioavailability. This is most likely due to a bypass of first-pass metabolism as this study suggests that approximately 40% of the absorbed loratadine was absorbed via the oral mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Loratidine) Noehr-Jensen et al (2006) reported that the oral bioavailability of loratadine from the chewing gum formulation was 3-fold higher compared with tablet and smelt tablet formulations. This was attributed to the fact that buccal absorption from the chewing gum formulation by-passes the traditional first pass effect from the gastrointestinal tract absorption.…”
Section: Selected Interesting Applications Of Salivary Analysismentioning
confidence: 98%
“…Loratidine) Noehr-Jensen et al (2006) reported that the oral bioavailability of loratadine from the chewing gum formulation was 3-fold higher compared with tablet and smelt tablet formulations. This was attributed to the fact that buccal absorption from the chewing gum formulation by-passes the traditional first pass effect from the gastrointestinal tract absorption.…”
Section: Selected Interesting Applications Of Salivary Analysismentioning
confidence: 98%
“…The pharmacokinetic results provide proof of concept that Loratadine formulated as a buccoadhesive wafer results in a statistically significant increase in its bioavailability, probably due to absorbed through buccal mucosa and reduction of first-pass metabolism (Noehr-Jensen et al, 2006).…”
Section: Pharmacokinetic Studymentioning
confidence: 56%
“…Earlier reports had revealed that formulation of Loratadine as a medicated chewing gum results in an almost threefold increase in relative bioavailability. This is due to the fact that approximately 40% of the absorbed Loratadine was absorbed via the oral mucosa and thereby bypassing first-pass metabolism [6]. Hence, it is an attempt to prepare pharmaceutical wafers of Loratadine with an aim to lessen the lag time and enhance the onset of action.…”
Section: Introductionmentioning
confidence: 99%